Design and field evaluation of hill-drop pneumatic central cylinder direct-seeding machine for hybrid rice - Wang, Baolong; Luo, Xiwen; Wang, Zaiman; Zheng, Le; Zhang, Minghua; Dai, Yizheng; Xing, He (International Journal of Agricultural and Biological Engineering, 2018)
To meet the requirement of the precision direct-seeding for hybrid rice, this study aimed to design a hill-drop pneumatic central cylinder direct-seeding machine to sow ten rows at a time. A series of orthogonal experiments were conducted to investigate the performance of the cylinder seeder. The influences of the hole diameters, degree of vacuum, and rotational speed of the cylinder were tested on JPS-12 computer-vision seeding test platform, and the rotational speed of 10-50 r/min, diameter of 135 mm and a negative pressure of 1.0-2.0 kPa were employed. Test results showed that the optimal parameter combination was a vacuum of 2.0 kPa and a hole diameter of 2.0 mm (straight hole), with a rotational speed of 30 r/min. The probability of (2±1) seeds in each hole was 95.3%, while the probability of seed-missing hole was 2.0%. A series of field experiments were then conducted to test the seeder performance according to China National Standard Test Methods, and the field test results showed that for the hill-drop pneumatic central cylinder direct-seeding machine, the probability of (2±1) seeds in each hill was 91.6%, while the probability of seed-missing hill was 2.7%. The yield data showed that the average effective panicle had 231.25 ears, the average seed setting rate was 9.92%, the average 1000-grain weight was 22.45 g, and the average yield was 7107.9 kg/hm2 that was 26.14% higher than the average yield of rice (5634.9 kg/hm2) of Guangdong Province in 2016. The results showed that the hill-drop pneumatic central cylinder direct-seeding machine for hybrid rice could be applied in practical precision rice seeding. Keywords: direct-seeding machine, hybrid rice, precision rice seeder, pneumatic cylinder, platform test, field test DOI: 10.25165/j.ijabe.20181106.4175 Citation: Wang B L, Luo X W, Wang Z M, Zheng L, Zhang M H, Dai Y Z, et al. Design and field evaluation of hill-drop pneumatic central cylinder direct-seeding machine for hybrid rice. Int J Agric & Biol Eng, 2018; 11(6): 33–40.